How regulation affects the relevance of bank-debt maturity as a control mechanism in developed countries. Issue 1 (2nd January 2017) - Vallelado, Eleuterio; Saona, Paolo; San Martín, Pablo
Abstract: Improvements in transparency at the country level have modified the relevance of bank debt maturity as a control mechanism. The novelty of this research is that we provide empirical evidence that the maturity of bank borrowing is contingent on the characteristics of the regulatory and the institutional setting about corporate governance. The main implication of our paper is that corporate governance rules have greater influence in civil-law countries than in common-law countries in promoting efficiency in the use of bank debt maturity. The value of this paper is that our results confirm that the implementation of similar regulations on transparency across countries with different legal systems favors the alignment of the role played by short-term bank debt in addressing asymmetric information, agency costs, and inefficient liquidation.